“Periodical Performance”: The Figure of the Editor in Nineteenth-Century Literary Magazines - Lendrum, Chris (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2010)
When John Scott and William Christie, representatives of the London Magazine and Blackwood’s Edinburgh Magazine, met in their fatal 1821 duel, the conflict was between more than two men with sullied reputations: it was a between the editor figures of two competing publications. This essay examines those editorial personae, the distinctive editorial voices crafted by individual journals, and how they played a crucial role in establishing a publication in the changing periodical market while simultaneously obscuring that process. Explicating the content and purpose of a publication, the editor figure established a journal’s unique identity in the marketplace, but it also established a point of contact between a periodical and its readers, an invitation that encouraged readers to feel included in the world of the publication. This affective connection socialized readers, incorporating them into the culture of the periodical as participants rather than just consumers, but it also created a brand for a publication, a unique voice that distinguished it (and its readers) from competing publications. While that combination of personal connection and commercial aspiration would appear to be mutually exclusive, I argue that the figure of the editor attempts to reconcile that contradiction, uniting the overt commercial ambition of a publication with a familiar, even friendly, presence. Just as crucially, however, it also reveals how periodicals of that time were caught in a period of transition, when the need to survive in an increasingly competitive print market clashed with older modes of literary consumption.